Konstrukcja ubezpieczenia rentowego jako ubezpieczenia na życie - Szczepańska, Magdalena (PRAWO i WIĘŹ, 2025)
This article presents the legal characteristics of disability insurance. It discusses its classification in light of applicable law and the criterion for this classification – the type of benefit paid. A detailed analysis of the essential aspects of this contract, such as the definition of the insured event, the insurer’s benefits, and the insurance premium, is provided. Various variants and varieties of disability insurance are also presented.